Synthetic plant virology for nanobiotechnology and nanomedicine - Steele, John F. C. (Wiley Interdiscip Rev Nanomed Nanobiotechnol, 2017)
Nanotechnology is a rapidly expanding field seeking to utilize nano‐scale structures for a wide range of applications. Biologically derived nanostructures, such as viruses and virus‐like particles (VLPs), provide excellent platforms for functionalization due to their physical and chemical properties. Plant viruses, and VLPs derived from them, have been used extensively in biotechnology. They have been characterized in detail over several decades and have desirable properties including high yields, robustness, and ease of purification. Through modifications to viral surfaces, either interior or exterior, plant‐virus‐derived nanoparticles have been shown to support a range of functions of potential interest to medicine and nano‐technology. In this review we highlight recent and influential achievements in the use of plant virus particles as vehicles for diverse functions: from delivery of anticancer compounds, to targeted bioimaging, vaccine production to nanowire formation. WIREs Nanomed Nanobiotechnol 2017, 9:e1447. doi: 10.1002/wnan.1447 For further resources related to this article, please visit the WIREs website.